(untitled) (Jurnal Destinasi Pariwisata, 2025)
This study aims to identify the cultural tourism potential of Puri Gede Penebel Saren Kaler and to formulate appropriate tourism development strategies to enhance its appeal as a cultural tourism destination in Penebel Village, Tabanan Regency. The research employs a descriptive qualitative approach, with data collection methods including observation, interviews, and documentation. Data analysis is conducted using the interactive model by Miles and Huberman, as well as SWOT analysis to formulate development strategies. The results indicate that Puri Gede Penebel Saren Kaler has high cultural tourism potential, particularly in terms of traditional Balinese architecture, historical royal heritage, and cultural activities related to the life of past nobility. However, the management and promotion of these attractions remain suboptimal. Based on the SWOT analysis, the recommended development strategies include maximizing the cultural and historical strengths of the puri to create unique tourism products, enhancing digital promotion, establishing partnerships with tourism stakeholders, and strengthening the capacity of local human resources. This study is expected to serve as a foundation for sustainable cultural tourism development planning at Puri Gede Penebel Saren Kaler and to contribute to the improvement of local community welfare through the tourism sector.